Decrease in phagocytosis capacity of hemocyte during spawning in Mytilus edulis: a pilot study - M. Fraser; P. Rault; P-H. Roumier; M. Fortier; C. André; P. Brousseau; F. Gagné; M. Fournier; C. Surette; C. Vaillancourt (MDPI AG, 2013)
Not available